Respuesta :

Answer: [tex]\$4.34[/tex]

Step-by-step explanation:

We have the following information:

Fredburguer [tex]F[/tex], milkshake [tex]M[/tex] and an order of fries [tex]f[/tex] costs [tex]\$3.72[/tex]:

[tex]F+M+f=\$3.72[/tex] (1)

One Fredburguer is equal to a milkshake plus orders of fries:

[tex]F=M+2f[/tex] (2)

Three milshakes is equal to a Fredburguer plus an order of fries:

[tex]3M=F+f[/tex] (3)

And we are asked: If we have a Fredburguer, a milkshake and two orders of fries, how much do we have to pay?

[tex]F+M+2f=x[/tex] (4)

Well with the first three equations we have a system of equations to solve. Let's begin by isolating [tex]F[/tex] from (3):

[tex]F=3M-f[/tex] (5)

Making (2)=(5):

[tex]M+2f=3M-f[/tex] (6)

Isolating [tex]f[/tex]:

[tex]f=\frac{2}{3}M[/tex] (7)

Substituting (7) in (2):

[tex]F=M+2(\frac{2}{3}M)[/tex] (8)

Isolating [tex]F[/tex]:

[tex]F=\frac{7}{3}M[/tex] (9)

Substituting (7) and (9) in (1):

[tex]\frac{7}{3}M+M+\frac{2}{3}M=\$3.72[/tex] (10)

Isolating [tex]M[/tex]:

[tex]M=\$0.93[/tex] (11) This is the cost of a Milkshake

Substituting (11) in (7):

[tex]f=\frac{2}{3}\$0.93[/tex] (12)

[tex]f=\$0.62[/tex] (13) This is the cost of an order of frieds

Substituting (11) in (9):

[tex]F=\frac{7}{3}\$0.93[/tex] (14)

[tex]F=\$2.17[/tex] (15) This is the cost of a Fredburguer

Substituting (11), (13) and  (15) in (4):

[tex]\$2.17+\$0.93+2(\$0.62)=x[/tex] (16)

Finally:

[tex]x=\$4.34[/tex] This is the cost of a Fredburguer, a milkshake and two orders of fries